Evaluating Alzheimer's Disease Progression by Modeling Crosstalk Network Disruption - Liu, Haochen; Wei, Chunxiang; He, Hua; Liu, Xiaoquan (Frontiers in Neuroscience, 2016)
Aβ, tau and P-tau have been widely accepted as reliable markers for Alzheimer’s disease (AD). The crosstalk between these markers forms a complex network. AD may induce the integral variation and disruption of the network. The aim of this study was to develop a novel mathematic model based on a simplified crosstalk network to evaluate the disease progression of AD. The integral variation of the network is measured by three integral disruption parameters. The robustness of network is evaluated by network disruption probability. Presented results show that network disruption probability has a good linear relationship with Mini Mental State Examination (MMSE). The proposed model combined with Support vector machine (SVM) achieves a relative high 10-fold cross-validated performance in classification of AD vs normal and mild cognitive impairment (MCI) vs normal (95% accuracy, 95% sensitivity, 95% specificity for AD vs normal; 90% accuracy, 94% sensitivity, 83% specificity for MCI vs normal). This research evaluates the progression of AD and facilitates AD early diagnosis.